Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2147/ijn.s138178
|View full text |Cite
|
Sign up to set email alerts
|

Kalopanacis Cortex extract-capped gold nanoparticles activate NRF2 signaling and ameliorate damage in human neuronal SH-SY5Y cells exposed to oxygen–glucose deprivation and reoxygenation

Abstract: Recently, environment-friendly synthesis of gold nanoparticles (GNPs) has been extensively explored by biologists and chemists. However, significant research is still required to determine whether “eco-friendly” GNPs are beneficial to human health and to elucidate the molecular mechanisms of their effects on human cells. We used human neuronal SH-SY5Y cells to show that treatment with Kalopanacis Cortex extract-capped GNPs (KC-GNs), prepared via an eco-friendly, fast, one-pot synthetic route, protected neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…One study in undifferentiated SH-SY5Y cells showed that the mitochondrial permeability transition pore is opened with OGD by translocation of P53 to mitochondria and activation of Cyclophilin D (Zhao et al 2013 ). The consequent mitochondrial membrane depolarization has been found in undifferentiated SH-SY5Y cells (n = 3) (Agudo-Lopez et al 2010 ; Park et al 2017 ; Wang et al 2018b ). Mitochondrial membrane permeabilization by opening of the mitochondrial permeability transition pore and loss of the mitochondrial membrane potential (MMP) has also been established in three studies in undifferentiated and in two studies differentiated SH-SY5Y cells (Lin et al 2020 ; Liu et al 2019a ; Park et al 2017 ; Sriwastva et al 2020 ; Wang et al 2019b ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…One study in undifferentiated SH-SY5Y cells showed that the mitochondrial permeability transition pore is opened with OGD by translocation of P53 to mitochondria and activation of Cyclophilin D (Zhao et al 2013 ). The consequent mitochondrial membrane depolarization has been found in undifferentiated SH-SY5Y cells (n = 3) (Agudo-Lopez et al 2010 ; Park et al 2017 ; Wang et al 2018b ). Mitochondrial membrane permeabilization by opening of the mitochondrial permeability transition pore and loss of the mitochondrial membrane potential (MMP) has also been established in three studies in undifferentiated and in two studies differentiated SH-SY5Y cells (Lin et al 2020 ; Liu et al 2019a ; Park et al 2017 ; Sriwastva et al 2020 ; Wang et al 2019b ).…”
Section: Resultsmentioning
confidence: 96%
“…The consequent mitochondrial membrane depolarization has been found in undifferentiated SH-SY5Y cells (n = 3) (Agudo-Lopez et al 2010 ; Park et al 2017 ; Wang et al 2018b ). Mitochondrial membrane permeabilization by opening of the mitochondrial permeability transition pore and loss of the mitochondrial membrane potential (MMP) has also been established in three studies in undifferentiated and in two studies differentiated SH-SY5Y cells (Lin et al 2020 ; Liu et al 2019a ; Park et al 2017 ; Sriwastva et al 2020 ; Wang et al 2019b ). Normal mitochondrial function was reduced in undifferentiated SH-SY5Y cells after OGD (Herrmann et al 2013 ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations